Autofuncões do modelo de Timoshenko em um sistema de duas vigas acopladas elasticamente - Pavlack, Bruna Silveira (2016)
This study aims to determine the eigenfunctions or vibration modes of a system composed of two beams coupled by an elastic layer and modeled mathematically by Timoshenko theory for beams. The study is conducted through modal analysis with a block matrix formulation and the vibration modes are written in terms of the fundamental matrix response, which is the fundamental solution of an impulsive initial value problem with matrix coe cients. The vibration modes are obtained for various boundary conditions in terms of the fundamental matrix solution. For the particular case of a double beam system supported-supported boundary conditions the modes are written in terms of the elementary functions trigonometric functions sine and cosine.